Tualang honey supplementation as cognitive enhancer in patients with schizophrenia - Rosliza, Yahaya; Azizul Fadzli, Wan Jusoh@Ab Rahim; Mohd Nizam, Zahary; Rahima, Dahlan@Mohd Shafie (2017)
Cognitive impairment in schizophrenia, including deficits in working memory, verbal learning and memory, predate the onset of frank psychosis and are stable throughout the the illness in most patients. Recently, tualang honey (TH) has been shown to improve immediate memory in postmenopausal women and rats. The present study aimed to investigate the effect of TH supplementation, on verbal learning and memory (VLM) in schizophrenia patients. A total of 80 schizophrenia patients in outpatient Psychiatric Clinic, Hospital Universiti Sains Malaysia, Kelantan were recruited between August to December 2014 and randomly assigned into two groups: TH (20 mg/d) and untreated control. Their VLM performances were assessed using the Malay version of the Auditory Verbal Learning Test (MVAVLT) before (week 0) and after (week 8) of intervention. Repeated measures analysis of covariance control for age, education and duration of illness was done using PASW version 20.0. A total of 28 subjects completed the study (TH group = 17, control group = 11). There were no significant differences in socio-demographic characteristics between the subjects in TH and control group except for the number of admission. The mean total learning and delayed recall within each group based on time were important for control with mean difference -4.18 (-7.63, -0.74), p=0.024 and -0.91 (-1.29,0.53), p < 0.01, respectively when controlled for covariate age, education and duration of illness. However, there were no significant differences in total learning and delayed recall scores between TH and control groups based on time even when controlled for covariate. Patient with schizophrenia who received TH supplementation for 8 weeks did not show significant improvement in the total learning (immediate memory/STM) and delayed recall (LTM) compared to control group.